2017
DOI: 10.1177/1933719116682877
|View full text |Cite
|
Sign up to set email alerts
|

miR-181b-5p Modulates Cell Migratory Proteins, Tissue Inhibitor of Metalloproteinase 3, and Annexin A2 During In Vitro Decidualization in a Human Endometrial Stromal Cell Line

Abstract: Decidualization is essential for successful embryo implantation and is regulated by concerted actions of growth factors and hormones. More recently, microRNAs, small RNA molecules that regulate posttranscriptional gene expression, have been implicated to play a role in the decidualization process. Of these microRNAs, miR-181b-5p has been associated with decidualization but its precise role and targets are not well established. To address this gap in our knowledge, we assessed the expression of miR-181b-5p, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In our study, 9 miRNAs were screened out (miRNA-378a-3p, miRNA-7-5p, miRNA-55-5p, miRNA-18a-5p, and miRNA-18b-5p were low expressed in decidual ECSCs, and miRNA-30d-5p, miRNA-30b-5p, miRNA-181c-5p, and miRNA-766-3p were highly expressed in decidual ECSCs). According to previous research reports, downregulation of mir-378a-3p [ 35 ], miR-181b-5p [ 36 ], and miR-155 [ 37 ] is beneficial to the formation of decidualization. This is in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 9 miRNAs were screened out (miRNA-378a-3p, miRNA-7-5p, miRNA-55-5p, miRNA-18a-5p, and miRNA-18b-5p were low expressed in decidual ECSCs, and miRNA-30d-5p, miRNA-30b-5p, miRNA-181c-5p, and miRNA-766-3p were highly expressed in decidual ECSCs). According to previous research reports, downregulation of mir-378a-3p [ 35 ], miR-181b-5p [ 36 ], and miR-155 [ 37 ] is beneficial to the formation of decidualization. This is in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-191 was found to be over-expressed in endometriomas tissue and to be a key regulator in the proliferation and the invasive properties of endometriosis cells (CRL7566) in vitro [ 32 ]. MiR-181b is involved in the regulation of the endometrial stromal cells’ migratory capacity [ 33 ]. The effect of miR-10b down-regulation in the endometrial cells may be realized via Syndecan-1, resulting in increased invasiveness [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the levels of miR-542-3p are lower in decidualizing versus normal human ESCs, and overexpression of miR-542-3p inhibits the expression of IGFBP1 , PRL, and WNT4 , suggesting an inhibitory role of miR-542-3p in decidualization [ 94 ]. It has also been reported that miR-181b-5p regulates the expression of cell migration associated proteins during decidualization [ 95 ]. Although TGFβ signaling regulates miRNA biosynthesis/expression [ 96 98 ], little is known about interactions between TGFβ signaling and miRNAs in the regulation of decidualization.…”
Section: Discussionmentioning
confidence: 99%